A Two-Dimensional Metal-Organic-Framework Formed From a Cobalt(II) Ion and a Bifunctional Ligand Exhibiting Thermochromic Behavior - Bommakanti, Suresh; Das, Samar K. (Frontiers in Materials, 2019)
We have synthesized a two-dimensional metal organic framework (MOF) containing compound [CoII0.5(Hbpydp)(H2O)]n·2nDMF (1) by solvothermal synthesis. Compound 1 has been characterized by routine spectral analyses including elemental analysis and unambiguously by single crystal X-ray crystallography. In the crystal structure, the cobalt(II) ion is characterized by an octahedral geometry, which consists of two nitrogen donors from two different ligands, two oxygen donors from two different ligands and two water oxygen atoms. Thus, each cobalt has CoO4N2 core octahedral moiety with all six donors coordinated in a monodentate fashion. This octahedral geometry of Co(II) in compound 1 is reflected by the characteristic orange coloration of compound 1 crystals. When the orange coloured crystals of compound 1 are heated at 150 oC under vacuum for 3 hours, the orange crystals become deep-purple in colour indicating some structural change around Co(II) with the loss of two coordinated water molecules resulting in the formation of compound 2 {[CoII0.5(Hbpydp)]n·2nDMF} (2). The deep-purple solid (compound 2), on keeping in a water-DMF solvent mixture at an ambient condition for 15 hrs (rehydration), is converted back to orange solid again (this regenerated compound denoted as 1R). This reversible conversion of 1 to 2 through 1R occurs in a crystal-to-amorphous-to-crystal (CAC) transformation. And the reversible thermochromism can be monitored by solid state electronic absorption spectroscopy (DRS) and thermogravimetric (TG) studies.